A Predictive Negative Sequence Current Control Algorithm for Voltage Imbalance Compensation and Power Oscillation Minimization under Unbalanced Conditions - Helaly, Nehal (Applied Science and Engineering Progress, 2023)
The predictive-based strategy employed in this paper allows an inverter to simultaneously inject positive and negative sequence reactive current to compensate for voltage imbalance, taking into account imbalance adverse effects on power oscillations. A suggested optimization cost function of a predictive-based controller is formulated to solve the trade-off problem between grid voltage support and voltage imbalance compensation by determining the optimal negative sequence reactive power to be injected to the reference current of a generator. The proposed predictive-based control strategy is evaluated under various distributed generation operating conditions in terms of injected active to reactive power ratio. Additionally, its performance is compared with the performance of an active power oscillations minimization (p̃-minimization) control strategy, where the active power oscillations due to reactive power disappear. In contrast with p̃-minimization control strategy, the proposed predictive-based strategy managed to reduce the active power oscillation. The adequacy of the proposed strategy is verified via simulations of a distributed energy resource (DER) grid-connected inverter under voltage imbalance caused by an unbalanced load. The simulation work presented in this paper was conducted using MATLAB/Simulink software. As a part of a smart inverter functions to preserve the energy supply under unbalanced conditions, this research would serve as a platform for studying the inverter optimal control of negative sequence component.